Algoritmos Genéticos en el Despacho de Energía Eléctrica - Betancourt Uscátegui, Álvaro (Ingeniería, 2001)
In this paper, we present an application of computational intelligence to resolve a problem of energy dispatch, showing how genetic algorithms can be useful in the solution of combinatorial optimization problems. The investigated problem is complex. It includes constraints related to the generator and the requirements of the load. Basically, it aims the selection of a set of generators, wich attempts to fully reach the hourly demand imposed y the load with a minimum cost.